Fundamentals of thermophotovoltaic energy conversion - Chubb, Donald L. (Elsevier, 2007)
This is a text book presenting the fundamentals of thermophotovoltaic(TPV) energy conversion suitable for an upper undergraduate or first year graduate course. In addition it can serve as a reference or design aid for engineers developing TPV systems. Mathematica design programs for interference filters and a planar TPV system are included on a CD-Rom disk. Each chapter includes a summary and concludes with a set of problems. The first chapter presents the electromagnetic theory and radiation transfer theory necessary to calculate the optical properties of the components in a TPV optical cavit.